Penerapan Model SQ3R untuk Meningkatkan Kemampuan Berpikir Kritis pada Pembelajaran IPS - Pramitha Hanny Ayuningtyas; Muhammad Labib; Joko Siswanto; Mohammad Qomarul Huda; Fitria Nur Inayah; Afidhatul Ummah (Kampus Akademik Publiser, 2025)
Critical thinking ability is an important skill in facing the challenges of the 21st century because it includes the ability to think logically, systematically, and rationally in evaluating information and solving problems. One of the effective learning models to foster these abilities is the SQ3R (Survey, Question, Read, Recite, Review) model. This study aims to describe the implementation steps, advantages, and disadvantages of the SQ3R model in social studies learning at Madrasah Aliyah Negeri 2 Rembang. The research used a qualitative approach with the subject of social studies teacher, and data collection techniques through interviews, observation, and documentation. The results showed that the steps of applying the SQ3R model include reading survey activities, preparing questions, reading and answering, and reviewing material to strengthen understanding. The advantages of the SQ3R model include the use of relatively short time, increased student concentration, active and directed learning, and repetition of reading that helps deep understanding. The disadvantages are that it requires more time and teacher skills in managing the class. It is concluded that the SQ3R model is effectively applied in social studies learning as a strategy to improve students' critical thinking skills in madrasah.